Research, Design and Develop a prototype of Multi-Spindle Drilling Head - Bui, Ngoc Tam; Tran, Van Dich (Old Journal, 2018)
In recent years, the study of machine tool technology has got strong attention to expand development in universities, research institute and also in industry. However, there are a few publications/papers related a design and application of the multi-spindle drilling which flexibly adjusts parameters such as the number and the position of holes. In this research, the author will present a new design of a multi-spindle drilling head that uses Cardan universal joint for driving in order to increase productivity, decrease product expenses. To check the principle of working after simulation we developed a prototype of Multi-Spindle drilling head in this research.